2017
DOI: 10.1108/mip-05-2017-0085
|View full text |Cite
|
Sign up to set email alerts
|

Identifying objectives for mega-event leveraging: a non-host city case

Abstract: Purpose The purpose of this paper is to identify strategic objectives that can be utilized by non-host communities to leverage the opportunities provided by mega sport events. The unique context and timing of this study facilitates discussion surrounding a particular non-host community and how it can plan relevant objectives to best identify appropriate leveraging mechanisms. Design/methodology/approach The study adopted a qualitative approach, drawing upon a case study of Kobe City, Japan, a non-host city o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Further to this, with the idea that regions outside of the host city will also benefit from the Games, understanding the challenges and opportunities to event leveraging for nonhost regions will be beneficial for stakeholders in a broader territory. Scholars in mega sporting events research have examined non-host cities/regions' experiences during the events in terms of economic effects (Daniels, 2007;Jones, 2005) and of management and social impacts in general (Beesley & Chalip, 2011;Bell & Gallimore, 2015;Chien, Kelly & Gill, 2017;Kellett, Hede, & Chalip, 2008;O'Brien & Gardiner, 2006). More recently, scholars have also suggested that there is a potential for non-host cities to maximise the positive impacts (albeit short-term) of the host country.…”
Section: Event Leverage In a Non-host Region: Challenges And Opportunmentioning
confidence: 99%
See 2 more Smart Citations
“…Further to this, with the idea that regions outside of the host city will also benefit from the Games, understanding the challenges and opportunities to event leveraging for nonhost regions will be beneficial for stakeholders in a broader territory. Scholars in mega sporting events research have examined non-host cities/regions' experiences during the events in terms of economic effects (Daniels, 2007;Jones, 2005) and of management and social impacts in general (Beesley & Chalip, 2011;Bell & Gallimore, 2015;Chien, Kelly & Gill, 2017;Kellett, Hede, & Chalip, 2008;O'Brien & Gardiner, 2006). More recently, scholars have also suggested that there is a potential for non-host cities to maximise the positive impacts (albeit short-term) of the host country.…”
Section: Event Leverage In a Non-host Region: Challenges And Opportunmentioning
confidence: 99%
“…More recently, scholars have also suggested that there is a potential for non-host cities to maximise the positive impacts (albeit short-term) of the host country. Chien, Kelly and Gill (2017) have argued that non-host regions might be in a position to take advantage of the event through enhancing destination brand equity, augmenting an existing event portfolio, and strengthening corporate and community-based networks. Fairley and Kelly (2017) demonstrated hosting pre-Games training camps in the non-host region can offer tourism benefits, and educational and sport programming opportunities.…”
Section: Event Leverage In a Non-host Region: Challenges And Opportunmentioning
confidence: 99%
See 1 more Smart Citation
“…They provide a wider environment that supports visitors' experiences during their travel to and stay in the destination. It is argued that non-host communities are sometimes in a favorable position to benefit from events when compared to host city residents because there is no initial investment and they can devote all resources to leveraging (Chien et al 2017). Therefore, few other studies (whether using the SET framework or not) have focused on non-host city residents' perceptions of sport event impacts on their communities (Chien et al 2017;Deccio and Baloglu 2002;Karadakis and Kaplanidou 2012;Lovegrove and Fairley 2017;Ritchie et al 2009) or countries (Liu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Sporting events are an indispensable part of today's society. They not only provide entertainment, but also promote economic development, social health, and even international diplomacy [5]. Sporting events are also considered to be able to provide host cities with many intangible benefits, such as the enhancement of community awareness, national or citizen pride, cultural identity, sports participation, and quality of life (hereafter referred to as QOL) [6].…”
Section: Introductionmentioning
confidence: 99%